The Counter-Urbanization Creative Class and the Sprout of the Creative Countryside: Case Studies on China’s Coastal Plain Villages - Miao Xumeı; Ye Chonglıang; Dai Haıdong; Sun Feihan (Journal of Economy Culture and Society)
The counter-urbanization creative class has gradually become an important factor in the revitalization of rural China, driving the steady and healthy development of the rural economy and society. This article explores the motivations and creative practices of the counter-urbanization creative class in the coastal plain villages of China to provide a reference for the development of rural society in China and other countries. Data from this study were obtained through qualitative research with participatory observations and semi-structured interviews. The study found that the rural areas around economically developed regions are increasingly favoured by the counter-urbanization creative class and have quickly become a platform for career development and realizing an ideal life; notably, rural creative industries have sprung up in China’s coastal plain villages. To date, the linkage between the counter-urbanization creative class and creative countryside is rarely explored in existing literature; thus, this paper produces a valuable exploration and addition to the area of the sprout of the creative countryside.